Voice Quality of VoIP in High Availability Environment - Hery Dian Septama; Ardian Ulvan; Jiri Hlavacek; Robert Bestak (IAES Indonesia Section, 2014)
The development of telecommunication technology specified the Internet Protocol (IP) based technology for the next generation network. Voice over Internet Protocol (VoIP) has been introduced to overcome future telephony demand. However, these rapid changes encountered some issues, and the most critical is how to provide the services availability and reliability equally to circuit based telephony. Virtualization is widely used not only for hardware efficiency and maintenance, but also for High Availability support. Virtualized environment provides the ability among servers to migrate or replicate into another machine, even when they are running their services, which is known as Live Migration. In this paper, the voice quality of VoIP service when running on the High Availability system in virtualized environment is studied and examined. The objective analysis by using quality of services (QoS) attributes is conducted as well as the subjective analysis using Mean Opinion Score (MOS). The work utilizes Xen® Hypervisor with modified Remus extensions to provide the High Availability environment. Remus approach using checkpoint based is deployed to copy the primary server to the backup server. A range of 40ms – 900ms has been applied as time interval of checkpoint. The results show that the mean jitter is 9,98 ms, packet loss 3,12% and MOS 3.61 for Remus 400ms checkpoint. MOS with different checkpoint time interval is also presented.